Identifikasi kutukebul (Hemiptera: Aleyrodidae) dari beberapa tanaman inang dan perkembangan populasinya - Purnama Hidayat; Yuliani Yuliani; Dewi Sartiami (Jurnal Entomologi Indonesia, 2006)
Whiteflies (Hemiptera: Aleyrodidae) can cause direct and indirect damages on plants, especially vegetables. There is only limited information regarding taxonomy and population dynamic of whiteflies attacking vegetables in Indonesia. This research is conducted to identify species of whitefly collected from chili pepper, tomato, and soybean, and to study their population dynamic. The information gathered from these studies will be useful to support whitefly management in the field. Based on morphology identification of the puparium collected directly from the host plants, there were four species of whitefly identified from chili pepper, tomato, and soybean in Bogor, Cianjur, and Sukabumi, i.e. Bemisia tabaci, Aleurodicus dispersus, Trialeurodes vaporariorum, and Dialeurodes sp. The presence of B. tabaci on chili pepper and tomato was associated with virus infection that causes yellowing and leaf curl disease. This population of B. tabaci tended to increase along with plant growth and generally reached the highest population when the plant was 60-70 days after planting.